Association between Angiotensinogen M235T Polymorphism and Preeclampsia in Iranian Pregnant Women. - Raha Afshariani; Jamshid Roozbeh; Maryam Sharifian; Mahbobeh Ghaedi; Alamtaj Samsami Dehaghani; Abbas Ghaderi (Tehran University of Medical Sciences, 2014)
Objective:To determine the possible association between the M235T variant of angiotensinogen gene and preeclampsia in Iranian preeclamtic women with hypertension during pregnancy. Mand methods:During a case control study, we used polymerase chain reaction-based restriction fragment length polymorphism (PCR-RFLP) analysis to investigate the association between M235T polymorphism in preeclamtic women compared to normotensive controls. Results:The M235T polymorphism was significantly associated with increased preeclampsia risk in the studied population as supported by a p value of 0.017 and chi-square value of 8.12. The frequency of mutated allele and genotype distribution showed a significant difference between preeclamtic women and control groups. Conclusion:The result indicates that the AGT M235T polymorphism plays a significant role in preeclampsia observed in selected Iranian preeclamtic women, and it can be considered as a major risk factor for preeclampsia.